ANALYSIS OF PRICE PERCEPTION, WORD OF MOUTH AND CUSTOMER EXPERIENCE ON CUSTOMER SATISFACTION AT BAMBU UNGU RESTO - Jihan Nabila; Ari Prabowo (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The F&B business is one of the most popular businesses among various segments of society, from the lower to the upper classes. This is because food and beverages are among the primary human needs. Increasingly fierce competition in the culinary industry requires businesses to understand the factors that influence customer satisfaction in order to maintain customer loyalty. This study aims to analyze the influence of price perception, word of mouth, and customer experience on customer satisfaction at Bambu Ungu Resto. The method used was a quantitative approach, with data collection techniques through the distribution of questionnaires to 120 respondents, who are Bambu Ungu Resto customers. Data were analyzed using statistical tests including t-tests and simultaneous tests. The results showed that partially, price perception had no significant effect on customer satisfaction, while word of mouth and customer experience had a positive and significant effect on customer satisfaction. Simultaneously, price perception, word of mouth, and customer experience had a positive and significant effect on customer satisfaction. These findings indicate that customer satisfaction is more influenced by perceived experience and recommendations from other consumers than by price.